Simultaneous enhancement of thermal conductivity and fire retardancy in polymer composites using P/N co-doped graphene microspheres - Park, Sangki; Kim, Nam Ryeol; Park, Minhyeok; Jang, Ji Wu; Yang, Cheol-Min (SPRINGER NATURE, 2025)
The rapid accumulation of heat in microelectronic and energy-storage devices critically limits their performance, lifespan, and safety and necessitates the development of multifunctional polymer composites with high thermal conductivity and fire retardancy. Herein, we present a simple and scalable spray-drying and heat-treatment approach for the fabrication of heteroatom-doped spherical reduced graphene oxide (PN-S-rGO) microspheres, which simultaneously delivers P/N co-doping and tunable crystallinity. The unique spherical morphology of PN-S-rGO facilitates an isotropic heat-transfer behavior, resulting in a high ratio of through-plane to in-plane thermal conductivity (0.9) in an epoxy composite. Furthermore, incorporating PN-S-rGO with graphene nanoplatelets (GnPs) as hybrid fillers significantly improves the filler dispersion, promotes an isotropic orientation, and enhances interfacial interactions between the filler and epoxy matrix, leading to efficient thermal pathways and robust fire-retardant networks. The optimized hybrid composite (10 wt% GnPs and 40 wt% PN-S-rGO treated at 800 degrees C) exhibited outstanding thermal conductivities of 3.72 W/mK (in-plane) and 1.74 W/mK (through-plane), along with excellent fire retardancy, as characterized by a limiting oxygen index of 29% and 75% reduction in the peak heat-release rate compared to that of pure epoxy. These simultaneous enhancements are attributable to mechanisms that operate in synergy, including contributions from thermal bridging, catalytic carbonization, gas-phase radical quenching, and the formation of compact char layers. This study demonstrated a promising strategy for the development of high-performance polymer composites for use in advanced thermal-management and fire-safe applications in next-generation electronics, electric vehicles, and energy-storage systems.